Chronic Obstructive Pulmonary Disease Exacerbations Increase the Risk of Subsequent Cardiovascular Events: A Longitudinal Analysis of the COPDGene Study - Han‐Mo Yang; Min Hyung Ryu; Vincent J. Carey; Gregory L. Kinney; John E. Hokanson; Mark T. Dransfield; Craig P. Hersh; Edwin K. Silverman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Cardiovascular disease (CVD) is the most important comorbidity in patients with chronic obstructive pulmonary disease (COPD). COPD exacerbations not only contribute to COPD progression but may also elevate the risk of CVD. This study aimed to determine whether COPD exacerbations increase the risk of subsequent CVD events using up to 15 years of prospective longitudinal follow‐up data from the COPDGene (Genetic Epidemiology of Chronic Obstructive Pulmonary Disease) study. Methods and Results The COPDGene study is a large, multicenter, longitudinal investigation of COPD, including subjects at enrollment aged 45 to 80 years with a minimum of 10 pack‐years of smoking history. Cox proportional hazards models and Kaplan‐Meier survival curves were used to assess the risk of a composite end point of CVD based on the COPD exacerbation rate. Frequent exacerbators exhibited a higher cumulative incidence of composite CVD end points than infrequent exacerbators, irrespective of the presence of CVD at baseline. After adjusting for covariates, frequent exacerbators still maintained higher hazard ratios (HRs) than the infrequent exacerbator group (without CVD: HR, 1.81 [95% CI, 1.47–2.22]; with CVD: HR, 1.92 [95% CI, 1.51–2.44]). This observation remained consistently significant in moderate to severe COPD subjects and the preserved ratio impaired spirometry population. In the mild COPD population, frequent exacerbators showed a trend toward more CVD events. Conclusions COPD exacerbations are associated with an increased risk of subsequent cardiovascular events in subjects with and without preexisting CVD. Patients with COPD experiencing frequent exacerbations may necessitate careful monitoring and additional management for subsequent potential CVD. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT00608764.